The Effect of Different Breeds and Ages on Semen Production at Singosari National Insemination Center - Ahmad Furqon; Irida Novianti; Wike Andre Septian; Rafika Febriani Putri; Chairdin Dwi Nugraha; Suyadi Suyadi (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2021)
The study was aimed to evaluate semen production on different levels of breeds and ages. A total of 28 bulls were used in this study constisted of 13 Bali bulls, 6 Simmental bulls, and 9 Ongole Grade bulls. The bull’s age was ranged from 2 to 5 years old. The semen was collected at Singosari National Artificial Insemination Center three times a week during 2018. Bull’s semen was evaluated macroscopically and microscopically. Parameters analyzed in this study were semen volume, sperm motility and concentration. The result showed that the different semen quality was found among the bulls at different ages. Semen volume increased with time until 5 years genarally. Bali cattle had the lowest sperm concentration. Ongole Grade cattle had higher sperm motility and lower semen volume. Simmental had the lowest sperm motility. Simmental cattle had semen volume more than 6 mL. In conclusion, Ongole Grade cattle have higher semen production than Bali and Simmental. The failed semen collection was found among the bulls but the qualified semen production based on SNI would be used in the process of frozen semen at Singosari National Artificial Insemination Center